(untitled) (Applied Biological Research, 2023)
Compounds isolated from organic waste are used as a source for the discovery of new entities against inflammation. Pineapple peel, a by-product of pineapple processing industry, is a thrown away waste. The current work aimed to study the in-vivo anti-inflammatory potential and determination of minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of ferulic acid - a phenolic acid isolated from the pineapple peel. Pseudomonas aeruginosa (ATCC 27853), Klebsiella pneumoniae (ATCC 700603), Bacillus cereus (ATCC 10876) and Staphylococcus aureus (ATCC 33591) were used for MIC and MBC study. Acute toxicity screened after giving graded doses of ferulic acid and analysed it’s in vivo anti-inflammatory potential using carrageenin induced paw oedema and xylene induced ear oedema in Wistar rats. NaCl and Indomethacin were used as both negative and positive controls, respectively. The isolated phenolic compounds significantly reduced inflammation at all the dose tested. From the study it may be concluded that the phenolic compound isolated from pineapple peel exhibit significant anti inflammatory activities and display strong bactericidal potentiality against Staphylococcus aureus and Pseudomonas aeruginosa indicating its anti inflammatory and bactericidal potential.